2020
DOI: 10.3390/agronomy10020195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Droplet Size Parameters on Droplet Deposition and Drift of Aerial Spraying by Using Plant Protection UAV

Abstract: In the field of pesticide spraying, droplet size is one of the most important factors affecting droplet deposition and drift. In order to study the effect of different droplet size parameters on droplet deposition distribution and drift of aerial spraying by using plant protection UAV, an aerial spraying test with the same spraying rate and different size droplets in rice canopy was carried out by using multi-rotor unmanned aerial vehicles (UAV) and four TEEJET nozzles with different orifice sizes (these dropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 26 publications
3
35
0
2
Order By: Relevance
“…D V0.1 represents the volume of a small droplet (10% of the total deposited volume). D V0.5 and D V0.9 represent the volume of medium-sized and large droplets, respectively [46,47] .…”
Section: Analysis Methodsmentioning
confidence: 99%
“…D V0.1 represents the volume of a small droplet (10% of the total deposited volume). D V0.5 and D V0.9 represent the volume of medium-sized and large droplets, respectively [46,47] .…”
Section: Analysis Methodsmentioning
confidence: 99%
“…This was different from our conclusion, which may be due to the different spray volume from our experiment. Chen et al [6] found that the percentage of spray coverage increased with the increase of the droplet size in the lower volume application. That was mainly caused by the drift of droplets.…”
Section: Percentage Of Spray Coveragementioning
confidence: 98%
“…It led to a low utilization rate and excessive spraying of pesticides and caused serious pesticide residues and environmental pollution [3][4][5] . According to reports, the use of pesticides in China was about 2.5 times the world average, and the arable area contaminated with pesticides accounted for about 1/10 of the arable area [6] .…”
Section: Introduction mentioning
confidence: 99%
“…As shown in Figure 11 b, the nozzle flow is mainly reflected in the deposition volume rather than the ratio. However, the small droplet diameter is easy to be affected by wind, and the large droplet leads to nonuniform deposition, as shown in Figure 11 c. Therefore, finding a suitable droplet diameter is necessary [ 18 ]. The distance between the propeller and the nozzle is related to the distribution of downwash wind field.…”
Section: Simulation Deposition Data Acquisitionmentioning
confidence: 99%